Letter to Governor Davis; from Jane Tolmach - Jane Tolmach:::::: (2000)
Letter to Governor Davis from Jane M. Tolmach sent on January 2, 2000. The purpose of this letter is to discuss the setback for Ventura County's first public college tying it to schedule with Stockton. Tolmach believes that it should be there college that should have top priority due having a large minority and low income population is discounted by the long commute. She also argues how they should receive capital funding for improvements to the campus, stating "It is time that we had our fair share". Tolmach is asking the governor to reconsider their funding this year.